Biological studies on woody leguminous invaders with special reference to Acacia mearnsii, A. melanoxylon and Paraserianthes lophantha - Pieterse, P. J (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1997.